A net stable funding ratio for Islamic banks and its impact on financial stability: An international investigation - Ashraf, Dawood; Rizwan, Muhammad Suhail; L’Huillier, Barbara (Journal of Financial Stability, 2016)
The Islamic Financial Services Board (IFSB) is the standard setting body for the Islamic banking industry. The IFSB, while endorsing the Basel III accord, modified the criteria to calculate the Net Stable Funding Ratio (NSFR) to cater for the unique aspects of the Islamic banking industry. In this paper, we calculated the modified NSFR of 136 Islamic banks from 30 jurisdictions between 2000 and 2013 and explored the potential impact the requirements of this ratio has on the financial stability of Islamic banks after controlling for bank, country, and market-specific variables. The empirical findings suggest that the modified NSFR has a positive impact on the financial stability of Islamic banks during the sample period. However, the marginal impact of the NSFR on stability diminishes as the size of the bank increases. The results remained robust after applying an alternative measure of stability and using an alternative estimation model based on an instrumental variable approach. These results validate the use of the IFSB’s modified NSFR for Islamic banks as a regulatory measure.